Image and Histologic Characterization of Intracranial Neoplasias - Martha Yudey Rodríguez Pino; Dianarelys Villafuerte Delgado; Thaimí Conde Cueto; Odalys Yanes Isray; Adelaida Martínez Godoy; Carlos Rafael Rivera Prieto (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Background: In Cuba, as in all developed countries, cancer is the second cause of death and among it the different types of intracranial neoplasms present a morbidity of 2-3 %. Among the diagnostic methods that can be used computarized tomography (CT-Scan) and magnetic resonance image (MRI) are the techniques that define the patient's diagnosis and treatment in this type of neoplasm. Objective: to characterize intracranial neoplasm. Methods: a retrospective descriptive study that included the discharged patients operated from central nervous system neoplasms was carried out at the University General Hospital "Dr. Gustavo Aldereguía Lima" from Cienfuegos province, from January 1st, 2003 to December 31st , 2007. All the patients had undergone a computarized tomography and had the histological post operatory diagnosis of primary or secondary neoplasms of the intracranial central nervous system. The variables under study were: sex, age, symptoms, location of the tumor, histological diagnosis, and tomography variables. Results: Neoplasms were predominant in males and in patients between 40 - 59 years of age. The most frequent symptom was headache, and its location in the frontal - parietal area. In 85, 7 % of the metastases a hypodense image was observed meanwhile in meningiomas a hyperdense image was seen. All tumors increased their density after contrast administration. The tomographic diagnosis coincided with the histological one in 85,7 % of gliomas, in 80 % of meningiomas and in 40 % of metastases. Conclusion: The computarized images of the cranium allow the inference of the histological type of intracranial neoplasms.